2016
DOI: 10.21037/jovs.2016.10.04
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic anatomic segmentectomies for lung cancer: technical aspects

Abstract: Although the interest for thoracoscopic sublobar resections (TSLR) is rising, its use for treating non-small cell lung carcinoma (NSCLC) is still controversial because publications dealing with survival and recurrence rate provide contradictory results. If applied to the resection of lung cancer, thoracoscopic segmentectomies must be performed according to oncological criteria. The aim of this technical paper is to give some technical details on thoracoscopic segmentectomies for the treatment of malignancies.O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Recently, segmentectomy for small non-small cell lung cancers has been widely performed and the validity of this procedure including video-assisted thoracoscopic surgery (VATS) segmentectomy has been established (1)(2)(3)(4). In a systematic meta-analytical review, Cao et al (5) found no significant difference in overall survival (OS) or disease-free survival (DFS) in the intentional or radical segmentectomy group compared with lobectomy, but significantly worse outcomes for palliative segmentectomy in the compromised group.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, segmentectomy for small non-small cell lung cancers has been widely performed and the validity of this procedure including video-assisted thoracoscopic surgery (VATS) segmentectomy has been established (1)(2)(3)(4). In a systematic meta-analytical review, Cao et al (5) found no significant difference in overall survival (OS) or disease-free survival (DFS) in the intentional or radical segmentectomy group compared with lobectomy, but significantly worse outcomes for palliative segmentectomy in the compromised group.…”
Section: Introductionmentioning
confidence: 99%
“…This decision was due to a shortage of annotated data sets to use for lymph node detection and a sensitivity (also known as the true positive rate or recall) in the region of 85% which was considered not reliable enough for clinical deployment ( 23 ). Neither CT or 3D-CT models incorporate the effects of intra-operative organ movement, for example caused by lung deflation, which can lead to spatial disorientation of the surgeon and/or induce landmark deviations from pre-operative data ( 16 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sublobar resections (SLR) include both non-anatomical wedge resections and anatomical resections of segments and subsegments with isolated division of both vascular and bronchial structures (i.e., anatomical segmentectomy). These procedures have specially spread within the last decade due to the diffusion and development of minimally invasive thoracic procedures, and the concept of "lung-sparing surgery", which means preserving as much lung parenchyma as possible [ Figure 1] [5,[21][22][23][24] .…”
Section: The Role Of Sublobar Resection In Lung Cancermentioning
confidence: 99%